Isolation and Growth Characterization of an Acrylamide-degrading E. cloacae strain UPM2021a Isolated from a Paddy Field (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Acrylamide is a suspected carcinogen and a global pollutant. The presence of acrylamide in the soil is a major source of this chemical. Microbe-mediated acrylamide breakdown as a bioremediation technique is gaining popularity across the world. Several bacteria capable of digesting acrylamide have been identified in paddy field soils. The best isolate was a bacterium identified tentatively as E. cloacae strain UPM2021a based on cultural, colony morphology and biochemical tests.  According to early studies, ideal growth parameters included a pH range of 6.5 and 7.5 and a temperature range of 25 to 35 degrees Celsius. Acrylamide dosages of up to 2500 mg/L were explored as a single nitrogen supply. The greatest growth occurs between 300 and 1000 mg/L of acrylamide, resulting in an approximate nett growth of 3 log CFU/mL when compared to the control. Growth was practically tolerated at 1700 mg/L, and growth stopped entirely at concentrations above 2000 mg/L. Toxic heavy metals such as mercury, copper, chromium, and cadmium hampered acrylamide development with mercury being the strongest inhibitor whilst other metal ions such as copper, cadmium, and chromium show from 30 to 50%  inhibition whilst lead was the least inhibiting. The relatively high tolerant of acrylamide makes this bacterium suitable for remediation of soil contaminated with acrylamide whilst its sensitivity to heavy metals chiefly mercury means metal-chelating or sequestering compounds must be added to soil contaminated with both acrylamide and heavy metals.
Keywords: Acrylamide; E. cloacae; Bioremediation; Paddy field; Characterization